Comparison of the applied 2 min modified laboratory test in the gymnastics disciplines during preparatory period - Gateva, M.; Tarnichkova, M.; Ivanov, N.; Andonov, K. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Due to the specifics of the gymnastics disciplines it is difficult to determine the dosage and also the effect of the applied load on the athletes. Commonly used tests, such as the VO2max, register only the aerobic capacity of the gymnasts. Gymnastics, as a complex noncyclic structured sport is proved (Gateva, 2009; Jeliazkov and Dasheva, 2002) to be in the anaerobic regime of work during the performed competitive programme - the routine. For that reason, the aim of this study is to create a laboratory model of the loading similar in intensity and duration to the gymnastics routines in order to compare the results between gymnastics disciplines. The test should cause the cardiovascular system to respond with 95% of the maximum HR which is the real value when executing a gymnastics routine (Gateva, 2009; Mineva et al. 2003). Methods: 60 high level athletes from 4 gymnastics disciplines (Rhythmic, Acrobatics (male & female), Aerobics and Aesthetic gymnastics) were tested in total. Step one: the gymnasts performed a maximal test (Modified Balke Treadmill Protocol - Athlete) with a constant speed of 8,4 km/h, 0% starting incline and increment of the incline with 0,6% every 30 sec. Step two: 2 min modified laboratory test (authors` test) with constant speed of 8,4 km/h with incline set up individually for each athlete through extrapolation of the HR towards 95% of its maximum. The indicators measured were VO2, HR, blood La, EPOC and related others. Results: The maximum HR reached at the end of the test varied from 181 to 186 b/min, the oxygen consumption was from 42 to 49 ml/kg/min and the blood lactate concentration went up to 10 mmol/l for all gymnastics discipline. Discussion: Applying test, same in duration and glycolytic requirements as the routine, shows the real effect of its execution. Attempts have been made in the past to calculate the energy cost of a gymnastics routine (Guidetti et al., 2000) but with extrapolation of the data from VO2max test. The results we gathered show that the different gymnastics disciplines require similar effort and energy consumption.